The Role of Entrepreneurial Orientations in Talent Retention Amongst Malaysian Engineers - Osman, Idris; Noordin, Fauziah; Mohd, Idaya Husna; Koe, Wei Loon (Universiti Utara Malaysia, 2018)
This paper examines the linkage between entrepreneurial orientation (EO) and talent retention amongst Malaysian engineers from the perspective of entrepreneurial orientation theory.A cross-sectional survey of 104 engineers from private organisations in Malaysia was conducted to test the hypothesised relationships between constructs.The population comprised graduate and professional engineers who were registered under the Board of Engineers Malaysia (BEM).The purposive sampling method was employed for data analysis purposes.Data was analysed using partial least square-structural equation modelling technique.The results of this study indicated a significant relationship between innovativeness, proactiveness, risk-taking, and competitive aggressiveness and the intention to stay (ITS).Autonomy was found not significant in predicting engineers’ ITS the same jobs.Engineers require EO to support their freedom of ideas and thoughts to exploit opportunities, produce creativity, and solve engineering task-related problems and uncertainty situations.EO dimensions can be used to predict engineers’ ITS current employments.This study provides crucial information for the organisations and policy makers to develop mechanisms and policies to enhance the engineers’ involvement of effective EO for increasing retention.